Analisis Perbandingan Kinerja Keuangan Pada Bank Syariah Bukopin Dan Bank Victoria Syariah Periode 2015-2019 - Mahdi Hendrich; Irsan; Masnoni; Dimas Try Handoko; Feni Fadilah (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2022)
Financial performance is a formal effort to evaluate the efficiency and effectiveness of the company in generating a certain profit and cash position. By measuring financial performance, it can be seen the prospects for the growth and development of the company's finances. The company is said to be successful if the company has achieved a certain predetermined performance. The purpose of this study was to analyze and compare the financial performance of Bukopin Syariah Bank and Victoria Syariah Bank based on the ratio of liquidity, solvency, profitability, and activity in 2015 to 2019. The type of research used in this research is descriptive quantitative approach. Data collection techniques are by using documentation techniques. The results of this study indicate that the financial performance based on liquidity ratios, solvency ratios, and activity ratios in 2015-2019 Bank Victoria Syariah Bukopin is better than the financial performance of Bank Syariah Bukopin. Although based on the profitability ratios of Bank Syariah Bukopin and Bank Victoria Syariah, they are still categorized as unhealthy. However, based on the 2015-2019 profitability ratios, Bank Syariah Bukopin has better financial performance compared to the profitability ratios of Bank Victoria Syariah.